Genetic Diversity Impacts Climate‐Induced Species Range Shifts - Brunno F. Oliveira; Romain Bertrand; Lise Comte; Jonathan Lenoir; Gaël Grenouillet; Lesley T. Lancaster; Jérôme Murienne; Sarah Diamond; Brett R. Scheffers; R. M. W. J. Bandara; Jake A. Lawlor; Nikki A. Moore; et al. (Ecology Letters, 2026)
Climate change threatens biodiversity when species cannot tolerate, adapt to, or track shifting environmental conditions to stay within their climatic niches. A major unresolved question is whether and how species' genetic diversity modulates these dynamics, buffering against range contractions or facilitating range expansions. To test this, we integrated the largest global databases of species range shifts and genetic diversity, encompassing 4673 range shift estimates for 1888 species with available genetic data, including insects, arachnids, birds, fish, and plants. We found that range shifting rates were significantly shaped by the interaction of genetic diversity and climate change velocity. Under rapid warming, species with higher genetic diversity exhibited reduced trailing edge contractions, likely reflecting enhanced evolutionary potential or reduced vulnerability to drift. Under moderate warming, species with higher genetic diversity shifted more rapidly at leading edges and range centroids, consistent with greater colonisation ability. Our study provides evidence that genetic diversity potentially enables persistence at the trailing edge and colonisation at the leading edge, with the magnitude of these effects varying depending on the velocity of climate change.

Extreme events drive rapid and dynamic range fluctuations - Lydia G. Soifer; Julie L. Lockwood; Jonas J. Lembrechts; Laura H. Antão; David H. Klinges; Rebecca A. Senior; Natalie C. Ban; Birgitta Evengard; Belen Fadrique; Sophie Falkeis; Alexa L. Fredston; Rob Guralnick; et al. (Trends in Ecology & Evolution, 2025)

Decision analysis shows scientific and economic value of community-based monitoring in Madagascar - Lydia G. Soifer; David H. Klinges; Lalatiana Randriamiharisoa; Brett R. Scheffers (Biological Conservation, 2025)

Identifying the factors that influence raccoon (Procyon lotor) and southeastern myotis (Myotis austroriparius) use of stormwater sewer systems - Alan A. Ivory II; Matt T. Hallett; Miguel A. Acevedo; Brett R. Scheffers; Kody M. Brock; Steve A. Johnson (Urban Ecosystems, 2025)

Reimagining species on the move across space and time - Alexa L. Fredston; Morgan W. Tingley; Montague H.C. Neate-Clegg; Luke J. Evans; Laura H. Antão; Natalie C. Ban; I-Ching Chen; Yi-Wen Chen; Lise Comte; David P. Edwards; Birgitta Evengard; Belen Fadrique; et al. (Trends in Ecology & Evolution, 2025)

Proximal microclimate: Moving beyond spatiotemporal resolution improves ecological predictions - David H. Klinges; J. Alex Baecher; Jonas J. Lembrechts; Ilya M. D. Maclean; Jonathan Lenoir; Caroline Greiser; Michael Ashcroft; Luke J. Evans; Michael R. Kearney; Juha Aalto; Isabel C. Barrio; Pieter De Frenne; et al. (Global Ecology and Biogeography, 2024)
Aim The scale of environmental data is often defined by their extent (spatial area, temporal duration) and resolution (grain size, temporal interval). Although describing climate data scale via these terms is appropriate for most meteorological applications, for ecology and biogeography, climate data of the same spatiotemporal resolution and extent may differ in their relevance to an organism. Here, we propose that climate proximity, or how well climate data represent the actual conditions that an organism is exposed to, is more important for ecological realism than the spatiotemporal resolution of the climate data. Location Temperature comparison in nine countries across four continents; ecological case studies in Alberta (Canada), Sabah (Malaysia) and North Carolina/Tennessee (USA). Time Period 1960–2018. Major Taxa Studied Case studies with flies, mosquitoes and salamanders, but concepts relevant to all life on earth. Methods We compare the accuracy of two macroclimate data sources (ERA5 and WorldClim) and a novel microclimate model ( microclimf ) in predicting soil temperatures. We then use ERA5, WorldClim and microclimf to drive ecological models in three case studies: temporal (fly phenology), spatial (mosquito thermal suitability) and spatiotemporal (salamander range shifts) ecological responses. Results For predicting soil temperatures, microclimf had 24.9% and 16.4% lower absolute bias than ERA5 and WorldClim respectively. Across the case studies, we find that increasing proximity (from macroclimate to microclimate) yields a 247% improvement in performance of ecological models on average, compared to 18% and 9% improvements from increasing spatial resolution 20‐fold, and temporal resolution 30‐fold respectively. Main Conclusions We propose that increasing climate proximity, even if at the sacrifice of finer climate spatiotemporal resolution, may improve ecological predictions. We emphasize biophysically informed approaches, rather than generic formulations, when quantifying ecoclimatic relationships. Redefining the scale of climate through the lens of the organism itself helps reveal mechanisms underlying how climate shapes ecological systems.

Reading tea leaves worldwide: Decoupled drivers of initial litter decomposition mass‐loss rate and stabilization - Judith M. Sarneel; Mariet M. Hefting; Taru Sandén; Johan van den Hoogen; Devin Routh; Bhupendra S. Adhikari; Juha M. Alatalo; Alla Aleksanyan; Inge H. J. Althuizen; Mohammed H. S. A. Alsafran; Jeff W. Atkins; Laurent Augusto; et al. (Ecology Letters, 2024)
The breakdown of plant material fuels soil functioning and biodiversity. Currently, process understanding of global decomposition patterns and the drivers of such patterns are hampered by the lack of coherent large‐scale datasets. We buried 36,000 individual litterbags (tea bags) worldwide and found an overall negative correlation between initial mass‐loss rates and stabilization factors of plant‐derived carbon, using the Tea Bag Index (TBI). The stabilization factor quantifies the degree to which easy‐to‐degrade components accumulate during early‐stage decomposition (e.g. by environmental limitations). However, agriculture and an interaction between moisture and temperature led to a decoupling between initial mass‐loss rates and stabilization, notably in colder locations. Using TBI improved mass‐loss estimates of natural litter compared to models that ignored stabilization. Ignoring the transformation of dead plant material to more recalcitrant substances during early‐stage decomposition, and the environmental control of this transformation, could overestimate carbon losses during early decomposition in carbon cycle models.

Bringing traits back into the equation: A roadmap to understand species redistribution - Lise Comte; Romain Bertrand; Sarah Diamond; Lesley T. Lancaster; Malin L. Pinsky; Brett R. Scheffers; J. Alex Baecher; R. M. W. J. Bandara; I‐Ching Chen; Jake A. Lawlor; Nikki A. Moore; Brunno F. Oliveira; et al. (Global Change Biology, 2024)
Ecological and evolutionary theories have proposed that species traits should be important in mediating species responses to contemporary climate change; yet, empirical evidence has so far provided mixed evidence for the role of behavioral, life history, or ecological characteristics in facilitating or hindering species range shifts. As such, the utility of trait‐based approaches to predict species redistribution under climate change has been called into question. We develop the perspective, supported by evidence, that trait variation, if used carefully can have high potential utility, but that past analyses have in many cases failed to identify an explanatory value for traits by not fully embracing the complexity of species range shifts. First, we discuss the relevant theory linking species traits to range shift processes at the leading (expansion) and trailing (contraction) edges of species distributions and highlight the need to clarify the mechanistic basis of trait‐based approaches. Second, we provide a brief overview of range shift–trait studies and identify new opportunities for trait integration that consider range‐specific processes and intraspecific variability. Third, we explore the circumstances under which environmental and biotic context dependencies are likely to affect our ability to identify the contribution of species traits to range shift processes. Finally, we propose that revealing the role of traits in shaping species redistribution may likely require accounting for methodological variation arising from the range shift estimation process as well as addressing existing functional, geographical, and phylogenetic biases. We provide a series of considerations for more effectively integrating traits as well as extrinsic and methodological factors into species redistribution research. Together, these analytical approaches promise stronger mechanistic and predictive understanding that can help society mitigate and adapt to the effects of climate change on biodiversity.

Determining the sustainability of legal wildlife trade - Alice Hughes; Mark Auliya; Sandra Altherr; Brett Scheffers; Jordi Janssen; Vincent Nijman; Chris R. Shepherd; Neil D'Cruze; Emerson Sy; David P. Edwards (Journal of Environmental Management, 2023)

Association of reproductive traits with captive‐ versus wild‐sourced birds in trade - Oscar Morton; Brett R. Scheffers; Torbjørn Haugaasen; David P. Edwards (Conservation Biology, 2023)
The wildlife trade is a billion‐dollar global business, involving millions of people, thousands of species, and hundreds of millions of individual organisms. Unravelling whether trade targets reproductively distinct species and whether this preference varies between captive‐ and wild‐sourced species is a crucial question. We used a comprehensive list of all bird species traded, trade listings and records kept in compliance with the Convention on International Trade in Endangered Species (CITES), and a suite of avian reproductive parameters to examine whether wildlife trade is associated with particular facets of life history and to examine the association between life‐history traits and captive‐ and wild‐sourced traded volumes over time. Across all trade, CITES listing, and CITES trade, large birds were more likely to be traded and listed, but their longevity and age at maturity were not associated with CITES listing or trade. We found species across almost the full range of trait values in both captive and wild trade between 2000 and 2020. Captive trade volumes clearly associated with relatively longer lived and early‐maturing species; these associations remained stable and largely unchanged over time. Trait–volume associations in wild‐sourced trade were more uncertain. Only body mass had a clear association, and it varied from negative to positive over time. Although reproductive traits were important in captive‐sourced trade, species‐level variation dominated trade, with even congeneric species varying greatly in volume despite similar traits. The collection and incorporation of trait data into sustainability assessments of captive breeding facilities are crucial to ensure accurate quotas and guard against laundering.

Precipitation drives species accumulation whereas temperature drives species decline in Himalayan vertebrates - Yiming Hu; Luke Gibson; Huijian Hu; Zhifeng Ding; Zhixin Zhou; Weiqi Li; Zhigang Jiang; Brett R. Scheffers (Journal of Biogeography, 2022)
Aim Many studies have explored taxon‐specific richness patterns with elevation, but few have concurrently evaluated different mechanisms to explain elevational patterns across multiple taxa. We used a novel, cross‐taxa approach to study species richness patterns combined with a framework that tests drivers of species accumulation versus decline along the elevational gradient in the Himalayas. Location The Himalayas. Taxon Mammals, birds and amphibians. Methods We used geographical and elevational data of 314 mammals, 842 breeding birds and 147 amphibians to investigate species richness patterns across elevational and geographical spaces. We divided the elevational species richness gradient into segments of species accumulation versus species decline by piecewise linear regressions. We used path analysis to disentangle the direct and indirect effects of the predictors on species richness for the overall pattern and its divided segments. We test the asymmetry of main drivers between the accumulation and decline segments of richness by iteration procedure. Results Species richness for most taxa tracks an elevational hump‐shaped distribution. The dominant driver of the overall pattern varied by taxa and in context to subregion. Across taxa, precipitation best predicts the accumulation of species richness, whereas temperature best predicts the decline in species richness. Moreover, temperature and precipitation can affect species richness indirectly through productivity, showcasing a large interactional effect of climate and productivity on species richness. Main conclusions Resource allocation of the ecosystem and requirements of the species differ between the lower and upper elevation segments but remain consistent across the overall gradient. The resources essential for promoting diversity and mediating stochastic processes are directly tied to precipitation at the process of species accumulation and temperature at the process of species richness decline. Our findings support the existing theory in climate change science that reduced precipitation combined with increasing temperature may cause species extinction in the species‐rich lowlands.

Correction to: Large, old trees define the vertical, horizontal, and seasonal distributions of a poison frog - Edmund W. Basham; Macario González-Pinzón; Angel Romero-Marcucci; Noah Carl; J. Alex Baecher; Brett R. Scheffers (Oecologia, 2022)

Large, old trees define the vertical, horizontal, and seasonal distributions of a poison frog - Edmund W. Basham; Macario González-Pinzón; Angel Romero-Marcucci; Noah Carl; J. Alex Baecher; Brett R. Scheffers (Oecologia, 2022)

Global maps of soil temperature - Jonas J. Lembrechts; Johan van den Hoogen; Juha Aalto; Michael B. Ashcroft; Pieter De Frenne; Julia Kemppinen; Martin Kopecký; Miska Luoto; Ilya M. D. Maclean; Thomas W. Crowther; Joseph J. Bailey; Stef Haesen; et al. (Global Change Biology, 2022)
Research in global change ecology relies heavily on global climatic grids derived from estimates of air temperature in open areas at around 2 m above the ground. These climatic grids do not reflect conditions below vegetation canopies and near the ground surface, where critical ecosystem functions occur and most terrestrial species reside. Here, we provide global maps of soil temperature and bioclimatic variables at a 1‐km 2 resolution for 0–5 and 5–15 cm soil depth. These maps were created by calculating the difference (i.e. offset) between in situ soil temperature measurements, based on time series from over 1200 1‐km 2 pixels (summarized from 8519 unique temperature sensors) across all the world's major terrestrial biomes, and coarse‐grained air temperature estimates from ERA5‐Land (an atmospheric reanalysis by the European Centre for Medium‐Range Weather Forecasts). We show that mean annual soil temperature differs markedly from the corresponding gridded air temperature, by up to 10°C (mean = 3.0 ± 2.1°C), with substantial variation across biomes and seasons. Over the year, soils in cold and/or dry biomes are substantially warmer (+3.6 ± 2.3°C) than gridded air temperature, whereas soils in warm and humid environments are on average slightly cooler (−0.7 ± 2.3°C). The observed substantial and biome‐specific offsets emphasize that the projected impacts of climate and climate change on near‐surface biodiversity and ecosystem functioning are inaccurately assessed when air rather than soil temperature is used, especially in cold environments. The global soil‐related bioclimatic variables provided here are an important step forward for any application in ecology and related disciplines. Nevertheless, we highlight the need to fill remaining geographic gaps by collecting more in situ measurements of microclimate conditions to further enhance the spatiotemporal resolution of global soil temperature products for ecological applications.

Niche lability mitigates the impact of invasion but not urbanization - Jesse B. Borden; Stephanie Bohlman; Brett R. Scheffers (Oecologia, 2022)

Arboreality drives heat tolerance while elevation drives cold tolerance in tropical rainforest ants - Lily Leahy; Brett R. Scheffers; Stephen E. Williams; Alan N. Andersen (Ecology, 2022)
Determining how species thermal limits correlate with climate is important for understanding biogeographic patterns and assessing vulnerability to climate change. Such analyses need to consider thermal gradients at multiple spatial scales. Here we relate thermal traits of rainforest ants to microclimate conditions from ground to canopy (microgeographic scale) along an elevation gradient (mesogeographic scale) and calculate warming tolerance to assess climate change vulnerability in the Australian Wet Tropics Bioregion. We test the thermal adaptation and thermal niche asymmetry hypotheses to explain interspecific patterns of thermal tolerance at these two spatial scales. We tested cold tolerance (CT min ), heat tolerance (CT max ), and calculated thermal tolerance range (CT range ), using ramping assays for 74 colonies of 40 ant species collected from terrestrial and arboreal habitats at lowland and upland elevation sites and recorded microclimatic conditions for one year. Within sites, arboreal ants were exposed to hotter microclimates and on average had a 4.2°C (95% CI: 2.7–5.6°C) higher CT max and 5.3°C (95% CI: 3.5–7°C) broader CT range than ground‐dwelling ants. This pattern was consistent across the elevation gradient, whether it be the hotter lowlands or the cooler uplands. Across elevation, upland ants could tolerate significantly colder temperatures than lowland ants, whereas the change in CT max was less pronounced, and CT range did not change over elevation. Differential exposure to microclimates, due to localized niche preferences, drives divergence in CT max , while environmental temperatures along the elevation gradient drive divergence in CT min . Our results suggest that both processes of thermal adaptation and thermal niche asymmetry are at play, depending on the spatial scale of observation, and we discuss potential mechanisms underlying these patterns. Despite the broad thermal tolerance range of arboreal rainforest ants, lowland arboreal ants had the lowest warming tolerance and may be most vulnerable to climate change.

The dangers of misrepresenting wildlife trade: response to Natusch et al. 2021 - David P. Edwards; Neil D'Cruze; Sandra Altherr; Alice Hughes; Jordi Janssen; Vincent Nijman; Stesha A. Pasachnik; Brett R. Scheffers; Chris R. Shepherd; Emerson Sy; Mark Auliya (Conservation Biology, 2021)

Community‐wide seasonal shifts in thermal tolerances of mosquitoes - Brunno F. Oliveira; Wendtwoin I. G. Yogo; Daniel A. Hahn; Jiang Yongxing; Brett R. Scheffers (Ecology, 2021)
The broadening in species’ thermal tolerance limits and breadth from tropical to temperate latitudes is proposed to reflect spatial gradients in temperature seasonality, but the importance of seasonal shifts in thermal tolerances within and across locations is much less appreciated. We performed thermal assays to examine the maximum and minimum critical temperatures (CT max and CT min , respectively) of a mosquito community across their active seasons. Mosquito CT min tracked seasonal shifts in temperature, whereas CT max tracked a countergradient pattern with lowest heat tolerances in summer. Mosquito thermal breadth decreased from spring to summer and then increased from summer to autumn. We show a temporal dichotomy in thermal tolerances with thermal breadths of temperate organisms in summer reflecting those of the tropics (“tropicalization”) that is sandwiched between a spring and autumn “temperatization.” Therefore, our tolerance patterns at a single temperate latitude recapitulate classical patterns across latitude. These findings highlight the need to understand the temporal and spatial components of thermotolerance variation better, including plasticity and rapid seasonal selection, and the potential for this variation to affect species responses to climate change. With summers becoming longer and increasing winter nighttime temperatures, we expect increasing tropicalization of species thermal tolerances in both space and time.

Designing countrywide and regional microclimate networks - Jonas J. Lembrechts; Jonathan Lenoir; Brett R. Scheffers; Pieter De Frenne (Global Ecology and Biogeography, 2021)
Issue Climate change, and its impacts on ecological, agricultural and other societal systems, is most often studied by relying on temperature data derived from countrywide weather‐station networks. Yet, these data do not capture microclimates, those arising from soil, vegetation and topography, at spatial scales relevant to the majority of organisms on Earth. We argue that a unified strategy is missing to design regional or countrywide networks to measure microclimates and thus provide ecologically relevant and sound climate data, for instance for modelling biodiversity and ecosystem functions. Evidence Here, we develop an integrative framework to design effective microclimate networks for potential implementation at the country level. With the dawn of novel low‐cost sensor technologies and modelling techniques it is time for designing standardized microclimate networks. We make an important step forward in that regard by providing hands‐on training to generate an optimal sensor distribution to capture as much microclimate diversity as possible at the regional or country scale. Conclusions By implementing our framework to design countrywide or regional microclimate networks, strategically positioned to capture a representative picture of microclimates available within the focal country or region, governments could lay the foundation for the development of a next generation of modelling and synthesis of landscapes, to serve a range of societal needs now and into the future as climate change accelerates.

Forest microclimates and climate change: Importance, drivers and future research agenda - Pieter De Frenne; Jonathan Lenoir; Miska Luoto; Brett R. Scheffers; Florian Zellweger; Juha Aalto; Michael B. Ashcroft; Ditte M. Christiansen; Guillaume Decocq; Karen De Pauw; Sanne Govaert; Caroline Greiser; et al. (Global Change Biology, 2021)
Forest microclimates contrast strongly with the climate outside forests. To fully understand and better predict how forests' biodiversity and functions relate to climate and climate change, microclimates need to be integrated into ecological research. Despite the potentially broad impact of microclimates on the response of forest ecosystems to global change, our understanding of how microclimates within and below tree canopies modulate biotic responses to global change at the species, community and ecosystem level is still limited. Here, we review how spatial and temporal variation in forest microclimates result from an interplay of forest features, local water balance, topography and landscape composition. We first stress and exemplify the importance of considering forest microclimates to understand variation in biodiversity and ecosystem functions across forest landscapes. Next, we explain how macroclimate warming (of the free atmosphere) can affect microclimates, and vice versa, via interactions with land‐use changes across different biomes. Finally, we perform a priority ranking of future research avenues at the interface of microclimate ecology and global change biology, with a specific focus on three key themes: (1) disentangling the abiotic and biotic drivers and feedbacks of forest microclimates; (2) global and regional mapping and predictions of forest microclimates; and (3) the impacts of microclimate on forest biodiversity and ecosystem functioning in the face of climate change. The availability of microclimatic data will significantly increase in the coming decades, characterizing climate variability at unprecedented spatial and temporal scales relevant to biological processes in forests. This will revolutionize our understanding of the dynamics, drivers and implications of forest microclimates on biodiversity and ecological functions, and the impacts of global changes. In order to support the sustainable use of forests and to secure their biodiversity and ecosystem services for future generations, microclimates cannot be ignored.

Patterns of ant activity and nesting ecology depend on flooding intensity in a Neotropical floodplain - Emily Khazan; Jelena Bujan; Brett R. Scheffers (International Journal of Tropical Insect Science, 2020)

SoilTemp: A global database of near‐surface temperature - Jonas J. Lembrechts; Juha Aalto; Michael B. Ashcroft; Pieter De Frenne; Martin Kopecký; Jonathan Lenoir; Miska Luoto; Ilya M. D. Maclean; Olivier Roupsard; Eduardo Fuentes‐Lillo; Rafael A. García; Loïc Pellissier; et al. (Global Change Biology, 2020)
Current analyses and predictions of spatially explicit patterns and processes in ecology most often rely on climate data interpolated from standardized weather stations. This interpolated climate data represents long‐term average thermal conditions at coarse spatial resolutions only. Hence, many climate‐forcing factors that operate at fine spatiotemporal resolutions are overlooked. This is particularly important in relation to effects of observation height (e.g. vegetation, snow and soil characteristics) and in habitats varying in their exposure to radiation, moisture and wind (e.g. topography, radiative forcing or cold‐air pooling). Since organisms living close to the ground relate more strongly to these microclimatic conditions than to free‐air temperatures, microclimatic ground and near‐surface data are needed to provide realistic forecasts of the fate of such organisms under anthropogenic climate change, as well as of the functioning of the ecosystems they live in. To fill this critical gap, we highlight a call for temperature time series submissions to SoilTemp, a geospatial database initiative compiling soil and near‐surface temperature data from all over the world. Currently, this database contains time series from 7,538 temperature sensors from 51 countries across all key biomes. The database will pave the way toward an improved global understanding of microclimate and bridge the gap between the available climate data and the climate at fine spatiotemporal resolutions relevant to most organisms and ecosystem processes.

Vertical stratification collapses under seasonal shifts in climate - Edmund W. Basham; Brett R. Scheffers (Journal of Biogeography, 2020)
Aim Tropical forests are vertically complex, and offer unique niche opportunities in the form of climate, habitat and resource gradients from ground to canopy. Rainforest species organize within this vertical spatial gradient and recent macroecological research suggests that the highest levels of vertical stratification occur in structurally complex and climatically stable tropical rainforests. However, although the classical view of the tropics is that of aseasonality, particularly in temperature, there is strong seasonality in rainfall. Thus, we predict considerable variation in vertical stratification in time, characterized by a seasonal restructuring of communities across vertical space. Location Sierra Llorona, Colón Province, Panama. Taxon Amphibians. Methods We performed 121 ground‐to‐canopy surveys across the wet and dry seasons for amphibians. Using a bootstrap simulation method we calculated species‐specific and community‐wide vertical height and abundance shifts between seasons. Separately, we tested the importance of vertical height and season on the vertical distribution of species using a redundancy analysis, and employed linear models to explore turnover in species composition across vertical height between seasons. Results Our results show a clear downward shift of 5 m in height in amphibian communities from the wet season to dry season. We also observe significant changes in species composition across vertical strata in both seasons, driven primarily by nestedness in the dry season (loss of species over height) and genuine turnover in the wet season (loss and addition of species over height). Main conclusions The exploitation of canopy microhabitats and resources in the wet season resulted in complex patterns of stratification, whereas drying flattened the distribution and simplified the composition of arboreal communities. As such, pattern and process in the vertical dimension is not static in time but rather exists as a dichotomy with inverse patterns between wet and dry seasons. Complex, multidimensional distributions of diverse rainforest communities can be simplified by climatic constraints – an important consideration as anthropogenic climate change increases the magnitude of seasonal swings in temperature and precipitation.

Historical environmental stability drives discordant niche filling dynamics across phylogenetic scales - Brunno F. Oliveira; Jeffry M. Flenniken; Robert P. Guralnick; Stephen E. Williams; Brett R. Scheffers (Journal of Biogeography, 2020)
Aim Regional diversity can increase owing to either the packing of species within regional niche space or the expansion of regional niche space. Yet, the primary factors dictating these dynamics remain poorly understood. Here, we assess the relative influence of current environmental conditions (net primary productivity, NPP) versus historic environmental stability over the Last Glacial Maximum on niche filling patterns of vertebrates (mammals, birds, amphibians and reptiles) in the Australian Wet Tropics (AWTs). Location Australian Wet Tropics. Taxon Vertebrates (mammals, birds, amphibians and reptiles). Methods We measured patterns of niche filling (niche packing vs. niche expansion) as the standardized departure of observed functional diversity (FD) from its null expectation. We fitted spatial models for vertebrates, and for each constituent class (mammals, birds, amphibians and reptiles) separately, to evaluate the relative effects of NPP and environmental stability on species richness and niche filling patterns. Results Historical environmental stability had a greater effect than NPP on species richness and niche filling patterns. However, the directionality of this effect depended on phylogenetic scale, with vertebrates exhibiting niche packing while each constituent class (except reptiles) exhibited niche expansion with increasing environmental stability. Main Conclusion Intra‐class competition presumably leads to niche differentiation and expansion, whereas the overlap of functional traits among species from different classes leads to niche packing. That environmental stability over millennia is associated with an expanding niche space across multiple vertebrate classes suggests that the accumulation of FD within communities requires long recovery times.

Bird’s nest fern epiphytes facilitate herpetofaunal arboreality and climate refuge in two paleotropic canopies - Christa M. Seidl; Edmund W. Basham; Lydou R. Andriamahohatra; Brett R. Scheffers (Oecologia, 2020)

Decoupled erosion of amphibians’ phylogenetic and functional diversity due to extinction - Brunno F. Oliveira; Brett R. Scheffers; Gabriel C. Costa (Global Ecology and Biogeography, 2020)
Aim It has been argued that the loss of phylogenetic diversity (PD) from species extinctions will result in concomitant loss of functional diversity (FD). As a result, species extinction undermines not only unique evolutionary history, but also ecosystem function and stability. Using data from > 6,000 amphibian species globally, we assess the potential erosion of PD and FD as a result of extinction. Location Global. Time period From the present day to the next 100 years. Major taxa studied Amphibians (Anura, Caudata and Gymnophiona). Methods We simulated future biogeographical patterns of extinction based on International Union for Conservation of Nature (IUCN) threat status, and estimated the loss of PD and FD accordingly. We used null models to determine the extent to which extinctions may result in disproportional losses of PD and FD relative to random extinction. Using spatial regressions, we tested whether the loss of PD can predict the loss of FD. Results Although spatial patterns of current amphibian PD and FD were similar, extinctions did not retain this similarity. The magnitude of such a decoupling varied widely in space, with most of the global assemblages losing more FD than PD. Main conclusion This study challenges the assumption that extinctions should yield comparable loss of PD and FD. Species may not be equivalent in the amount of unique evolutionary history and ecological functions that would be lost if they become extinct. Designing conservation strategies based on a single dimension of biodiversity has the danger of leading to misinformed outcomes.

Changing Thermal Landscapes: Merging Climate Science and Landscape Ecology through Thermal Biology - A. Justin Nowakowski; Luke O. Frishkoff; Mickey Agha; Brian D. Todd; Brett R. Scheffers (Current Landscape Ecology Reports, 2018)

Divergent melanism strategies in Andean butterfly communities structure diversity patterns and climate responses - Pauline C. Dufour; Keith R. Willmott; Pablo S. Padrón; Shuang Xing; Timothy C. Bonebrake; Brett R. Scheffers (Journal of Biogeography, 2018)
Aim Geographic distributions are driven by a combination of species sensitivity and exposure to climate. We quantified colour lightness, a trait that mediates the interaction between sensitivity and exposure, of diverse butterfly communities to test whether colour lightness is associated with community assembly across climate‐elevation gradients. Location Ecuadorian Andes. Methods We used a long‐term dataset of museum specimens for two of the most species‐rich genera of Pieridae butterflies in Ecuador, Catasticta and Leptophobia . Within a phylogenetic framework, we examined how communities assemble based on four traits across elevation: colour lightness, species‐specific heating rate, maximum temperature (under experimental solar exposure), and elevation breadth. Results We found that colour lightness in both genera was related to elevation, but the two genera exhibited opposite patterns; Catasticta are darker and Leptophobia are lighter with increasing elevation. The two genera have opposite configurations of body and body + wings colour lightness but achieve comparable thermoregulation, assessed via their rates of heating under experimental solar exposure. Additionally, we found that the phylogenetic signal for colour lightness was strong, and that patterns between traits and elevation held after correction for phylogeny in Catasticta but not in Leptophobia . Main conclusions The two genera exhibit divergent relationships between elevational and colour lightness patterns, with evidence that these relationships evolved multiple times in Catasticta . Communities from these two genera have likely been shaped by selection on different traits, with Catasticta colour lightness more responsive to temperature than Leptophobia . The observed geographic patterns of colour lightness in both body + wings ( Catasticta ) and body ( Leptophobia ) correspond strikingly with the distribution of montane cloud forests. Habitat fragmentation and cloud lifting from climate change documented across the Andes may therefore significantly impact communities through increased exposure to solar radiation, highlighting the complexity of conserving these diverse montane communities.

Widespread Degradation of a Vernal Pool Network in the Southeastern United States: Challenges to Current and Future Management - Jonathan P. Evans; Kristen K. Cecala; Brett R. Scheffers; Callie A. Oldfield; Nicholas A. Hollingshead; David G. Haskell; Benjamin A. McKenzie (Wetlands, 2017)

Vertical (arboreality) and horizontal (dispersal) movement increase the resilience of vertebrates to climatic instability - Brett. R. Scheffers; Luke Shoo; Ben Phillips; Stewart L. Macdonald; Alex Anderson; Jeremy VanDerWal; Collin Storlie; Arnaud Gourret; Stephen E. Williams (Global Ecology and Biogeography, 2017)
Aim Species that respond favourably to environmental change tend to be mobile or dispersive. Living within trees has some benefits over life on the ground. Species that move vertically within forest canopies can take advantage of increased complexity and resource availability, which should correspond to increased resilience to environmental variability and change. Here we show that two modes of movement, arboreality and horizontal dispersal, across an entire bioregional vertebrate fauna in the rain forests of Australia are associated with measures of historical environmental stability. Location Wet Tropics, Queensland, Australia. Time period Historical (c. 20,000 years ago) and current (1990‐2009). Major taxa studied Mammal, bird, reptile, and frog species. Methods We analysed vertebrate distribution for 195 species and trait data from 20 years of standardized sampling. We derived an arboreality index (i.e., the extent of vertical habitat used by each species) from a large database of field observations combined with expert opinion scores on arboreality. We compared community‐wide trends in arboreality and their horizontal dispersal potential with historical climate since the Last Glacial Maximum ( c . 20,000 years ago) and current climate over 20 years of the recent past (1990–2009). Results Vertical (arboreality) and horizontal (dispersal) movement were positively correlated, and both were negatively correlated with environmental stability. We found that arboreal species dominate communities in historically unstable areas, and these areas have both low richness and low endemism. Further, we show that low‐ and high‐altitude arboreal species experience similar thermal regimes, whereas low‐ and high‐altitude ground‐dwelling species experience little overlap in thermal regimes. Main conclusion Higher variability and overlap in temperature among rain forest canopies suggests less geographical separation in tolerable conditions for arboreal taxa when compared with ground‐dwelling taxa. Increased ecological plasticity in horizontal and vertical movement as well as exposure and pre‐selection to high temperature variability appears to allow arboreal species to exploit climatically uncertain areas, a capacity that may serve them well in responding to future climate change.

Impacts of hunting on tropical forests in Southeast Asia - Rhett D. Harrison; Rachakonda Sreekar; Jedediah F. Brodie; Sarah Brook; Matthew Luskin; Hannah O'Kelly; Madhu Rao; Brett Scheffers; Nandini Velho (Conservation Biology, 2016)
Although deforestation and forest degradation have long been considered the most significant threats to tropical biodiversity, across Southeast Asia (Northeast India, Indochina, Sundaland, Philippines) substantial areas of natural habitat have few wild animals (>1 kg), bar a few hunting‐tolerant species. To document hunting impacts on vertebrate populations regionally, we conducted an extensive literature review, including papers in local journals and reports of governmental and nongovernmental agencies. Evidence from multiple sites indicated animal populations declined precipitously across the region since approximately 1980, and many species are now extirpated from substantial portions of their former ranges. Hunting is by far the greatest immediate threat to the survival of most of the region's endangered vertebrates. Causes of recent overhunting include improved access to forests and markets, improved hunting technology, and escalating demand for wild meat, wildlife‐derived medicinal products, and wild animals as pets. Although hunters often take common species, such as pigs or rats, for their own consumption, they take rarer species opportunistically and sell surplus meat and commercially valuable products. There is also widespread targeted hunting of high‐value species. Consequently, as currently practiced, hunting cannot be considered sustainable anywhere in the region, and in most places enforcement of protected‐area and protected‐species legislation is weak. The international community's focus on cross‐border trade fails to address overexploitation of wildlife because hunting and the sale of wild meat is largely a local issue and most of the harvest is consumed in villages, rural towns, and nearby cities. In addition to improved enforcement, efforts to engage hunters and manage wildlife populations through sustainable hunting practices are urgently needed. Unless there is a step change in efforts to reduce wildlife exploitation to sustainable levels, the region will likely lose most of its iconic species, and many others besides, within the next few years.

Large body size for metamorphic wood frogs in urban stormwater wetlands - Brett R. Scheffers; Cynthia A. Paszkowski (Urban Ecosystems, 2016)

Limited genetic structure in a wood frog (Lithobates sylvaticus) population in an urban landscape inhabiting natural and constructed wetlands - Benjamin L. S. Furman; Brett R. Scheffers; Murdoch Taylor; Corey Davis; Cynthia A. Paszkowski (Conservation Genetics, 2016)

Effect of laurel wilt invasion on redbay populations in a maritime forest community - Jonathan P. Evans; Brett R. Scheffers; Matthew Hess (Biological Invasions, 2014)

Microhabitats reduce animal's exposure to climate extremes - Brett R. Scheffers; David P. Edwards; Arvin Diesmos; Stephen E. Williams; Theodore A. Evans (Global Change Biology, 2014)
Extreme weather events, such as unusually hot or dry conditions, can cause death by exceeding physiological limits, and so cause loss of population. Survival will depend on whether or not susceptible organisms can find refuges that buffer extreme conditions. Microhabitats offer different microclimates to those found within the wider ecosystem, but do these microhabitats effectively buffer extreme climate events relative to the physiological requirements of the animals that frequent them? We collected temperature data from four common microhabitats (soil, tree holes, epiphytes, and vegetation) located from the ground to canopy in primary rainforests in the Philippines. Ambient temperatures were monitored from outside of each microhabitat and from the upper forest canopy, which represent our macrohabitat controls. We measured the critical thermal maxima ( CT max ) of frog and lizard species, which are thermally sensitive and inhabit our microhabitats. Microhabitats reduced mean temperature by 1–2 °C and reduced the duration of extreme temperature exposure by 14–31 times. Microhabitat temperatures were below the CT max of inhabitant frogs and lizards, whereas macrohabitats consistently contained lethal temperatures. Microhabitat temperatures increased by 0.11–0.66 °C for every 1 °C increase in macrohabitat temperature, and this nonuniformity in temperature change influenced our forecasts of vulnerability for animal communities under climate change. Assuming uniform increases of 6 °C, microhabitats decreased the vulnerability of communities by up to 32‐fold, whereas under nonuniform increases of 0.66 to 3.96 °C, microhabitats decreased the vulnerability of communities by up to 108‐fold. Microhabitats have extraordinary potential to buffer climate and likely reduce mortality during extreme climate events. These results suggest that predicted changes in distribution due to mortality and habitat shifts that are derived from macroclimatic samples and that assume uniform changes in microclimates relative to macroclimates may be overly pessimistic. Nevertheless, even nonuniform temperature increases within buffered microhabitats would still threaten frogs and lizards.

The effects of urbanization on North American amphibian species: Identifying new directions for urban conservation - Brett R. Scheffers; Cynthia A. Paszkowski (Urban Ecosystems, 2012)